2016
DOI: 10.1155/2016/3635209
|View full text |Cite
|
Sign up to set email alerts
|

Jin Fu Kang Oral Liquid Inhibits Lymphatic Endothelial Cells Formation and Migration

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Jin Fu Kang (JFK), an oral liquid prescription of Chinese herbal drugs, has been clinically available for the treatment of non-small cell lung cancer (NSCLC). Lymphangiogenesis is a primary event in the process of cancer development and metastasis, and the formation and migration of lymphatic endothelial cells (LECs) play a key role in the lymphangiogenesis. To assess the activity of stromal cell-derived factor-1 (SDF-1) and the coeffect of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…He et al provided an experimental evidence that Jinfukang suppressed the differentiation and migration of lymphatic endothelial cells (LECs) in vitro, which is closely related to the tumor lymph-angiogenesis. This inhibitory effect might be via regulation of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4) and vascular endothelial growth factor (VEGF)-C/VEGF receptor-3 (VEGFR)-3 axes [ 55 ]. Que et al elucidated that Jingfukang can induce DNA damage in circulating tumor cell (CTC)-TJH-01 cells through the ROS-mediated ataxia telangiectasia mutated (ATM)/ATM and Rad3-related (ATR)-p53 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al provided an experimental evidence that Jinfukang suppressed the differentiation and migration of lymphatic endothelial cells (LECs) in vitro, which is closely related to the tumor lymph-angiogenesis. This inhibitory effect might be via regulation of stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4) and vascular endothelial growth factor (VEGF)-C/VEGF receptor-3 (VEGFR)-3 axes [ 55 ]. Que et al elucidated that Jingfukang can induce DNA damage in circulating tumor cell (CTC)-TJH-01 cells through the ROS-mediated ataxia telangiectasia mutated (ATM)/ATM and Rad3-related (ATR)-p53 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the other study used JFK-containing serums which were prepared from JFK-dosed rats and applied to the in vitro assays. Using serum drug concentration might directly reflect the drug efficacy since crude herbal medicine exhibit complex compositions and need series of biotransformation before performing their pharmacological actions [ 55 ]. As with experiment methods, there were seven in vitro studies while the other nine used both the in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that Jingfukang can promote DDP-induced apoptosis in lung cancer cells [21, 22]. In addition, other studies have also found that Jinfukang can inhibit lymphatic endothelial cell formation and migration and inhibit the lung tumor mass via the suppression of bone marrow-derived mesenchymal stem cell transformation and lung tumor lymphangiogenesis [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Given that traditional Chinese medicine is composed of multiactive components and possesses multitarget action feature, it can aim at multiple targets, exerting a systemic effect at the same time. Multitarget medicine has been proven to be particularly effective in treating complex diseases [ 1 , 27 29 ]. In this study, we found that FYC protected articular cartilage via numerous ways, including the reduction of ECM degradation factors, decrease in inflammatory mediator depression, and improvement of articular cartilage protective factor.…”
Section: Discussionmentioning
confidence: 99%